People management and knowledge management: conceptualization and applicability in health organizations - Melenchion, José Ricardo (O Mundo da Saúde, 2006)
This study had as its aim a discussion on the current concepts of people management in organizations and its applicability in health companies. The methodology used was based on a bibliographic survey. The results indicate a change of concepts in the human resources area, the evolution of the profile and the position of the human resources manager and the HR as a strategic partner. Conclu- sion: a necessity was perceived of the maintenance of a balance between change, innovation and transformation, on the one hand and between continuity and discipline on the other, and the HR must play a moderator role, respecting the achieved wisdom.